VD_FINDINFO Décision / 2016 / 772 vom 11. November 2016 - VD Tribunal cantonal (2016)
DÉTENTION PROVISOIRE, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, SOUPÇON | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 393 al. 1 let. c CPP (CH)